Developing tools to assess quality traits in beans for sustainable and nutritional foods in LAC - Gallego, Sonia; Orozco, Juan Camilo; Patiño, Gelver; Taleon, Victor; Andrade, Robert (2024)
Common bean is a staple crop in Latin America and the Caribbean (LAC) and Eastern-Southern Africa, where local preferences for specific varieties play a crucial role in their acceptance. Much of the importance of beans lies in their high contribution of proteins and minerals to the diet. In LAC thanks to strategies led by CIAT, new and better varieties of beans have been developed and released, with greater productivity, higher iron content, drought tolerance, etc. Traits such as color and shape, cooking time and taste are essential to assess their acceptability. On the other hand, nutritional quality is determined by their concentration of macronutrients (protein or amino acids, carbohydrates), micronutrients (minerals and vitamins) and other compounds that can have a nutraceutical or antinutritional action (phytates, phenolic compounds, sugars). Furthermore, it is important to analyze nutritional quality in terms of digestibility and its bioavailability. Each country in LAC has distinct cultural and culinary traditions that influence which types of beans are favored, shaping dietary habits and agricultural practices. Therefore, the evaluation of bean grain quality must be carried out from a comprehensive perspective that meets the interests and preferences of producers, traders, and consumers. Understanding relevant traits is essential for promoting sustainable production and enhancing food and nutritional security in the region. The Nutrition Quality and Food Processing Laboratory (NQL) of the Alliance of Bioversity International and CIAT has developed specific methodologies to assess these bean traits, with the aim of providing valuable information that fosters innovative connections between crop breeders, actors in the agri-food chain, nutrition and health specialists and other stakeholders, including the food industry and policy makers.